Penambahan DGR (Directional Ground Relay) Pada Recloser Untuk Menurunkan SAIDI / SAIFI DI ULP Lamongan - Fadjar Kurniadi; Ahmad Deni Aji; Guruh Diyuksamana (Energi & Kelistrikan, 2021)
The purpose of adding a DGR Relay to the Recloser is to improve the performance of the Recloser so that the network reliability value expressed by Saidi and Saifi is better. At ULP Lamongan, in general the protection on the installed Recloser is OCR and GFR relays. In systems with high resistance grounding, the performance of the recloser is not optimal, so it is necessary to add a DGR relay. The implementation of adding a DGR Relay to the Recloser at the Lamongan Customer Service Unit can reduce SAIDI by 86% and decrease SAIFI value by 58%.